NGO governance: the King IV Report on Corporate Governance as a servant leader - Marais, Kathleen Yvonne (University of the Free State, 2020)
The 2016 Life Esidimeni tragedy, which claimed the lives of more than 140 mental health care patients in South Africa’s Gauteng province, was a “wake-up call” for civil society to reform and improve the sector (USAID 2018: 210). The Life Esidimeni tragedy highlighted the lack of governance in civil society organisations and specifically in NGOs that operate in the health sector, where a people-centred approach is crucial. The aim of the study was to investigate the link between ethical leadership and good governance in the NGO sector by comparing the traits of servant leadership with the principles of the King IV Report on Corporate Governance with the aim of demonstrating how the traits of servant leadership are embedded into the King IV Report, thus linking leadership and good governance in one practical instrument that could assist NPOs operating in the health sector in establishing and maintaining a record of good governance while at the same time keeping a people-centred approach. The analysis was conducted at the hand of five themes found in the structure of the King IV Report, and the conclusion was reached that the main traits of servant leadership intersect with the principles the King IV Code in a manner that could ensure improved governance in the non-profit sector, which in turn could broaden democracy in South Africa.
Keywords: Dissertation (MGT (Governance and Political Transformation))--University of the Free State, 2020; Governance; Corporate governance; The King IV Report; Servant leadership; Civil society; Non-profit sector; Ubuntu; Stakeholders; Ethical leadership; Ethical culture